PERANCANGAN PERAHU LISTRIK BERTENAGA SURYA DI KOTA PONTIANAK - Joko Nursanto . (Faculty of Engineering, Universitas Tanjungpura, 2016)
Power Boats is a means of transportation in an environmentally friendly water using solar systems, which transform the energy of sunlight into electrical energy stored in the battery and later as an energy source to drive an electric boat engines. This electric boats as the development of renewable energy do not use fuel that is increasingly growing number of limited and expensive prices. Electric boats have a speed of 7 km / h and can operate for approximately 11.46 hours. The electric boats using solar panels solar Skytech SIM-100 wp, Trojan 31-GEL battery with a capacity of 102 Ah, Solar Charge Controller Shinyoku SC 990 (12V - 10A) engine powered boat Trolling Motor 0.50 pk made in China. Keywords: Power Boats, PLTS, Renewable Energy.